Small-scale Farmers’ Vulnerability to Climate Change in the Peruvian Andes (Alternautas, 2022)
Peru has been ranked as one of the most vulnerable countries in the world to the consequences of climate change (UNEP, 2013). Most of the world’s tropical glaciers (71%) are found in Peru (Vuille et al, 2008). During the past decades, scientists have observed the alarming impacts of global warming in the Peruvian Andes—thirty per cent of the glacier snowpack has been lost in a 30-year period (Urrutia & Vuille, 2009) and abnormal changes in seasonal precipitation patterns have been monitored (Sanabria et al, 2014). These changes in hydrological cycles pose a serious concern for populations living in the Andean lowland communities where glacier meltwater and precipitation provide a fundamental source of water. In some regions of the Andean highlands, rural populations already have restricted access to potable water and irrigation. Poor highland communities often have less capacity to respond to the increasing water scarcity due to weak infrastructure, low income, strong reliance on agriculture and limited opportunities for alternative livelihoods. It is, therefore, projected that livelihoods and the daily survival of rural populations in the Andes will be threatened as the water supply continues to decline (Mark et al, 2010). Myriad studies have been conducted on climate change in the Andean region from the standpoint of the natural sciences, revealing the biophysical threats climatic changes are posing to local ecosystems (Perez et al, 2010; Drenkahn et al, 2015). However, fewer studies have focused on climate vulnerability of local people in the rural highlands (Bury et al, 2011; Lynch, 2012).Andean highland populations have also suffered from political marginalization and discrimination for centuries in the Peruvian society, and some studies have suggested that climatic changes will further increase their vulnerability (Lynch, 2012; Rasmussen, 2015).